Integration of community health workers into health systems in developing countries: Opportunities and challenges. Issue 1 (1st January 2016) - Asweto, Collins Otieno; Alzain, Mohamed Ali; Andrea, Sebastian; Alexander, Rachel; Wang, Wei
Abstract : Background: Developing countries have the potential to reach vulnerable and underserved populations marginalized by the country's health care systems by way of community health workers (CHWs). It is imperative that health care systems focus on improving access to quality continuous primary care through the use of CHWs while paying attention to the factors that impact on CHWs and their effectiveness. Objective: To explore the possible opportunities and challenges of integrating CHWs into the health care systems of developing countries. Methods: Six databases were examined for quantitative, qualitative, and mixed-methods studies that included the integration of CHWs, their motivation and supervision, and CHW policy making and implementation in developing countries. Thirty-three studies met the inclusion criteria and were double read to extract data relevant to the context of CHW programs. Thematic coding was conducted and evidence on the main categories of contextual factors influencing integration of CHWs into the health system was synthesized. Results: CHWs are an effective and appropriate element of a health care team and can assist in addressing health disparities and social determinants of health. Important facilitators of integration of CHWs into health care teams are support from other health workers and inclusion of CHWs in case management meetings. Sustainable integration of CHWs into the health care system requires the formulation and implementation of polices that support their work, as well as financial and nonfinancial incentives, motivation, collaborative and supportive supervision, and a manageable workload. Conclusions: For sustainable integration of CHWs into health care systems, high-performing health systems with sound governance, adequate financing, well-organized service delivery, and adequate supplies and equipment are essential. Similarly, competent communities could contribute to better CHW performance through sound governance of community resources, promotion of inclusiveness and cohesion, engagement in participatory decision making, and mobilization of local resources for community welfare.